(untitled) (UTM Press - Edited Book, 2025)
Unlock the hidden potential of nature’s most abundant resource—biomass. Biomass Valorization and Applications takes readers on a journey through the latest innovations in transforming agricultural and industrial waste into valuable products for health, environmental, and industrial use. From eco-friendly adsorbents for dye removal to natural extracts for wound healing and food supplementation, this volume blends scientific theory with real-world impact. Each chapter offers a glimpse into cutting-edge techniques like supercritical fluid extraction, supported by insights into process mechanisms and industrial scalability. Designed for researchers, engineers, and students alike, this book inspires sustainable thinking while delivering practical tools for modern challenges in green technology and resource recovery.